Enhancement of Natural Convection Heat Transfer Using Magnetic Nanofluid in a Square Cavity - Noor Suhail Najm; Hadi O.Basher; Mohammed D.Salman (Wasit Journal of Engineering Sciences)
Researchers in heat transfer are paying close attention to nanofluids because of their potential as high-performance thermal transport media. In light of natural convection's enormous significance, the addition of nanoparticles significantly enhances the thermophysical properties of the nanofluids compared to the base fluid. In this study, numerical work was used to evaluate the influence of CuO nanoparticles on natural convection with the magnetohydrodynamic (MHD) flow in a square cavity. The hollow's left and right vertical walls were maintained at different temperatures, and the top and bottom walls of the cavity were each insulated. This numerical study applied a horizontal magnetic field with uniform strength. Results were obtained for a variety of Hartmann numbers ranging from 0–300, Rayleigh numbers going from 2.76E+8 to 6.89E+8, and solid volume fractions ranging from 0 to 1.5%. Results showed that the heat transfer coefficient and Nusselt number values decreased with the increase in the values of the Hartmann number, except for the heat transfer coefficients at Ha=100 and 150 were larger than the heat transfer coefficients at Ha= 0. The maximum heat transfer coefficient enhancement was 40.8% at 1.5% volume concentration of CuO nanoparticles, Ra= 6.7E+8 and Ha=100 compared to water at Ha=0. The maximum enhancement of the Nusselt number was found to be 28.5% at a 1.5% volume concentration of CuO nanoparticles Ra= 6.7E+8 and Ha=100 compared to water at Ha=0. At a 1.5% volume concentration of CuO nanoparticles, Ra= 6.7E+8 and Ha=100, the increase in the heat transfer coefficient was 56 %, and the rise in the Nusselt number was 43 % compared to water at Ha=100.